Modeling the yield curve with applications for government bonds - Kulíšková, Michaela (2018)
This bachelor thesis focuses on modeling the yield curves using two models: Nelson-Siegel and Nelson-Siegel-Svensson. We explain these two models in theoretical part of the thesis and apply them on our three countries - Netherlands, Slovenia and Czech Republic. Firstly, we estimate the coefficients for both models in R program. Subsequently, we use them and model the 3D graphs in matlab and examine the differences between them.The main contribution of this thesis is to compare the two mentioned models and decide witch can be better for fitting the yield curves using data from the secondary market. The results show that it is better to use the Nelson-Siegelmodel in order to more realistic approach.